(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Describing the clinical and subclinical characteristics of the breast cancer patient treated with Trastuzumab at Thong Nhat hospital. Subjects and methods: A retrospective study on 48 patients with breast cancer were treated with Trastuzumab at Thong Nhat hospital. Results: Mean age: 48.4 ± 3.4 years old. The 45-60 age group accounted for the largest proportion with 47.92%. Functional symptoms: the proportion of patients who self-examined the tumor accounted for the highest rate with 64.58%. There were 12.50% of patients with pain symptoms, 10.42% of patients with nipple discharge. Physical symptoms: tumor in the upper-external quadrant accounted for the largest percentage with 58.33%. The average size of the tumors was 2.78 ± 1.32 (cm). The main type of lesions was detected on ultrasound was local lesion with over 77.08% with an unknown boundary feature (66.67%) and invasive, accounting for 43.75%. Histopathological type accounted for the highest proportion was the invasive tubular carcinoma (79.92%). Histological degree accounted for the highest percentage was degree 2 with 45.83%. Stage II accounted for the highest rate with 39.58%, stage VI had the lowest rate with 10.42%. Conclusion: Common age of breast cancer patients was 45 - 60 years old, mainly the self-examined tumor, common breast tumors were found in the upper-external quadrant. On ultrasound, mainly the local lesion, the boundary was not clear. The histopathological type was the invasive tubular carcinoma.